2010
DOI: 10.1159/000320247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia in Elderly Living in Two Cities of Central Africa: The EDAC Survey

Abstract: Background: Data on dementia from low- and middle-income countries are still necessary to quantify the burden of this condition. This multicenter cross-sectional study aimed at estimating the prevalence of dementia in 2 large cities of Central Africa. Methods: General population door-to-door surveys were conducted in the districts of Bangui (Republic of Central Africa) and Brazzaville (Congo) in elderly aged ≧65 years. The subjects were screened with the Community Screening Interview for Dementia and the Five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 41 publications
8
94
3
2
Order By: Relevance
“…Prevalence was similarly low in rural Benin (2.4% age-standardized for age 65+ and 2.0% for age 60+ similarly estimated) (38). The prevalence in urban Benin was higher (4.3% and 3.5%) (40) and that recorded in cities in the Central African Republic (10.1% and 8.2%) and the Republic of the Congo (7.2% and 6.0%) was substantially higher (39).…”
Section: Dementia Subtypesmentioning
confidence: 78%
See 1 more Smart Citation
“…Prevalence was similarly low in rural Benin (2.4% age-standardized for age 65+ and 2.0% for age 60+ similarly estimated) (38). The prevalence in urban Benin was higher (4.3% and 3.5%) (40) and that recorded in cities in the Central African Republic (10.1% and 8.2%) and the Republic of the Congo (7.2% and 6.0%) was substantially higher (39).…”
Section: Dementia Subtypesmentioning
confidence: 78%
“…Subsequent studies from francophone countries in western and central Africa (38)(39)(40), and one further study from northern Nigeria (41) suggest a more variable prevalence, higher in urban than in rural sites, and higher in central compared with western Africa. The Nigerian study recorded a low prevalence that is consistent with findings from the earlier USA / Nigeria study (2.4% for those aged 65 and over, age-stan- suggested that the true prevalence at baseline was likely to be much closer to the 7.5% recorded for 10 / 66 dementia than the 0.9% prevalence according to DSM-IV criteria (20).…”
Section: Discussion -Prevalence Of Dementiamentioning
confidence: 99%
“…12,15,16,[18][19][20][21][22][23] In one paper, two studies were reported, and we considered these studies separately. 24 Because of considerable heterogeneity in methods (sampling and study design), population samples (age, health, socioeconomic status, geographical region and cultural background) and screening or diagnostic measures, we did not pool the data but report our findings in narrative form.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…24 Cognitive screening was performed using the CSI-D and 5-Word Test, adapted and presented in local languages. Diagnosis was confirmed by neurological examination and further psychometric testing in participants suspected of dementia (defined as a CSI-D score of < 25.5 of 30 or a 5-Word Test score of < 10 of 10).…”
Section: Central African Republic and Congomentioning
confidence: 99%
“…1 The estimation of patients who die with stroke in 2020 will increase 2 times of the record in 1990, especially in developing countries. 2,3 In Asian countries, stroke is the cause of death higher than the cardiovascular disease significantly.…”
Section: Introductionmentioning
confidence: 99%